Infrared neurostimulation in ex-vivo rat sciatic nerve using 1470 nm wavelength. (9th April 2021) - Cury, Joaquin; Vande Perre, Louis; Smets, Hugo; Stumpp, Lars; Vespa, Simone; Vanhoestenberghe, Anne; Doguet, Pascal; Delbeke, Jean; El Tahry, Riëm; Gorza, Simon-Pierre; Nonclercq, Antoine
Abstract: Objective. To design and implement a setup for ex-vivo optical stimulation for exploring the effect of several key parameters (optical power and pulse duration), activation features (threshold, spatial selectivity) and recovery characteristics (repeated stimuli) in peripheral nerves. Approach. A nerve chamber allowing ex-vivo electrical and optical stimulation was designed and built. A 1470 nm light source was chosen to stimulate the nerve. A photodiode module was implemented for synchronization of the electrical and optical channels. Main results . Compound neural action potentials (CNAPs) were successfully generated with infrared light pulses of 200–2000 µ s duration and power in the range of 3–10 W. These parameters determine a radiant exposure for stimulation in the range 1.59–4.78 J cm −2 . Recruitment curves were obtained by increasing durations at a constant power level. Neural activation threshold is reached at a mean radiant exposure of 3.16 ± 0.68 J cm −2 and mean pulse energy of 3.79 ± 0.72 mJ. Repetition rates of 2–10 Hz have been explored. In eight out of ten sciatic nerves (SNs), repeated light stimuli induced a sensitization effect in that the CNAP amplitude progressively grows, representing an increasing number of recruited fibres. In two out of ten SNs, CNAPs were composed of a succession of peaks corresponding to different conduction velocities. Significance. The reported sensitization effect could shed light on the mechanism underlying infrared neurostimulation. Our results suggest that, in sharp contrast with electrical stimuli, optical pulses could recruit slow fibres early on. This more physiological order of recruitment opens the perspective for specific neuromodulation of fibre population who remained poorly accessible until now. Short high-power light pulses at wavelengths below 1.5 µ m offer interesting perspectives for neurostimulation.